Insight into positional isomerism of N-(benzo[d]thiazol-2-yl)-o/m/p-nitrobenzamide: crystal structure, Hirshfeld surface analysis and interaction energy - Abdul Latiff, Aqilah; Chong, Yan Yi; Lee, Mark Wun Fui; Kassim, Mohammad (MDPI, 2020)
The functionalization of N-(benzo[d]thiazol-2-yl)benzamide with a nitro (NO2) substituent influences the solid-state arrangement, absorption and fluorescence properties of these compounds. Each of these compounds crystallised in a different crystal system or space group, namely a monoclinic crystal system with P21/n and C2/c space groups for o-NO2 and m-NO2 derivatives, respectively, and an orthorhombic crystal system (Pbcn space group) for p-NO2 derivative. The o-NO2 substituent with intrinsic steric hindrance engendered a distorted geometry. Conversely, the m-NO2 derivate displayed the most planar geometry among the analogues. The solid-state architectures of these compounds were dominated by the N−H···N and C−H···O intermolecular hydrogen bonds and were further stabilised by other weak interactions. The dimer synthons of the compounds were established via a pair of N−H···N hydrogen bonds. These findings were corroborated by a Hirshfeld surface analysis and two-dimensional (2D) fingerprint plot. The interaction energies within the crystal packing were calculated (CE-B3LYP/6-31G(d,p)) and the energy frameworks were modelled by CrystalExplorer17.5. The highly distorted o-NO2 congener synthon relied mainly on the dispersion forces, which included π–π interactions compared to the electrostatic attractions found in m-NO2. Besides, the latter possesses an elevated asphericity character, portraying a marked directionality in the crystal array. The electrostatic and dispersion forces were regarded as the dominant factors in stabilising the crystal packing.